Penerapan Metode Bermain Kartu Kata Dalam Meningkatkan Keterampilan Berbicara pada Anak Speech Delay Usia 5-6 Tahun di PAUD Darul ‘Ulum Kecamatan Pelabuhan Ratu Kabupaten Sukabumi - Faridah, Faridah; Awal Maulana, Redi; Elnawati, Elnawati (PT. Alahyan Publisher Sukabumi, 2025)
Developing children's language skills is an important thing to do. One of them is the ability of children to speak, speaking is a way done by humans to communicate and share information. Children's speaking skills must be trained and developed to the maximum to make it easier for children to learn and socialize. However, there are several factors that affect children's language development, one of which is speech delay (speech delay) caused by a lack of language stimulus. One of the efforts made to overcome these problems is the use of the storytelling method. This research was conducted with the aim of finding out the process of using the storytelling method in dealing with children's speech delay. This study uses a qualitative descriptive field research method. The research location is in PAUD Darul Ulum, PelabuhanRatu District, Sukabumi Regency. The research subjects included, teachers, principals, and 4 students of PAUD Darul Ulum speech delay obtained through observation, interviews, and documentation. This research process describes the efforts made by educators in handling children's speech delay, namely by using the storytelling method. This study uses the Classroom Action Research method with a total of 7 subjects in PAUD Darul Úlum, Pelabuhan Ratu District, Sukabumi Regency.